Comparison of maternal anxiety scores in pediatric intensive care unit and general ward parents - Lie Affendi Kartikahadi; Soetjiningsih Soetjiningsih; I Gusti Ayu Endah Ardjana; I Gusti Ayu Trisna Windiani (Indonesian Pediatric Society, 2012)
Background Hospitalization of a child is known to be a dreadfuland stressful situation for parents. One study reported thatadmitting a child to a general ward caused mild anxiety to mothers,while admitting a child to the pediatric intensive care unit (PICU)caused moderate anxiety to mothers.Objective To compare Hamilton anxiety scores of mothers whosechildren were admitted to the PICU to those of mothers whosechildren were admitted to the general ward.Methods A cross-sectional study was done on mothers ofchildren aged 1 month-12 years. Children were admitted toeither the intensive care unit or the general ward from October2010-January 2011. All subjects were assessed by Hamiltonanxiety scores and questioned for risk factors and other causesof maternal anxiety. Consecutive sampling was used to allocatethe subjects. Differences were considered statistically significantfor P < 0.05.Results Of the 72 subjects, the median Hamilton anxiety score inmothers of children admitted to the PICU was 20.5 (interquartilerange 14-29.75), higher than that of mothers of children admittedto the general ward (14, interquartile range 9-16.75). MannWhitneyU test revealed a statistically significant difference inscores between the two groups (P = 0.DO1). Ancova multivariateanalysis showed the admission location to be the only significantrelationship to Hamilton anxiety score (P = 0.0001).Conclusion Hamilton anxiety scores were higher for mothersof children admitted to the PICU than that of mothers withchildren admitted to the general ward. [Paediatr lndones.2012;52:95-8].